84=-6(-6+2p)

Simple and best practice solution for 84=-6(-6+2p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 84=-6(-6+2p) equation:


Simplifying
84 = -6(-6 + 2p)
84 = (-6 * -6 + 2p * -6)
84 = (36 + -12p)

Solving
84 = 36 + -12p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '12p' to each side of the equation.
84 + 12p = 36 + -12p + 12p

Combine like terms: -12p + 12p = 0
84 + 12p = 36 + 0
84 + 12p = 36

Add '-84' to each side of the equation.
84 + -84 + 12p = 36 + -84

Combine like terms: 84 + -84 = 0
0 + 12p = 36 + -84
12p = 36 + -84

Combine like terms: 36 + -84 = -48
12p = -48

Divide each side by '12'.
p = -4

Simplifying
p = -4

See similar equations:

| x-5(x-4)=3(x-8)-5 | | 1.75+0.3x=0.9x-2.5 | | -19(5-18z)= | | -36e+21e= | | .50x+.20y=3.90 | | 0.55x+0.05(18-x)=0.10(-11) | | -45=8(4x-7)+7(5x-8) | | -14(5+11r)= | | -(w+5)=-15 | | 7w+8w=208-13 | | 7-6x-3=-25+4x-11 | | 9(-6f-19)= | | x^2+3x=(2-x^2) | | 2k-6k+-8k= | | -3x+8=7x-52 | | (10m+8)-(6m-9)= | | -2(7x+6)=40 | | -3n+2+8n+1=5(-7+5n)-4(5n-3) | | 5b+17b= | | 5(11-7r)= | | -4+12m-1=10m-15-3m | | 60-6x=19x | | 7x-3=74 | | m^2+6m+13=0 | | -9x-5x-19=21 | | 7x-(4x-4)=25 | | 14(-11r+2)= | | -5a=21 | | 3(d-8)=9(9+2)+1 | | (13m+4)-(3m-5)= | | -6+1-3= | | Q=500+3p |

Equations solver categories